2D electrostatic energy harvesting device using a single shallow arched microbeam. (June 2021) - Ben Hassena, Mohamed Amin; Samaali, Hatem; Ouakad, Hassen M.; Najar, Fehmi
Abstract: We propose to use a shallow arched microbeam to design a compact 2D energy harvesting device using a single electrostatic transducer. The proposed design can transform any in-plane applied acceleration into motion of a variable capacitor whose movable electrode is linked to the shallow arched microbeam. A secondary electrode is placed to directly apply a force on the microbeam in order to tune its natural frequency to increase the amount of harvested energy. We derive the governing equations of the coupled system using the Hamilton's principle. The associated nonlinear differential equations are solved using a Galerkin technique. The frequency response curves are obtained for accelerations in different directions under several applied voltages. The model and the design are validated using a finite element model. In a second modeling approach, the system is coupled to a conditioning circuit based on pump-charge technique. The coupled system is solved for different excitation frequencies. It was observed that the input voltage can be doubled after a 16 s excitation, and that almost the triple of this value can be obtained for longer excitation times. The performance of the system is assessed by comparing its performances with other designs found in the literature. Highlights: New design of a 2D energy harvester using a single electrostatic transducer. The design transforms any in-plane acceleration into motion of a variable capacitor. The electromechanical analytical model is validated using a finite element model. The input voltage can be doubled after a 16 s excitation.